2000
DOI: 10.1021/ic0005285
|View full text |Cite
|
Sign up to set email alerts
|

[MoV12O302-OH)10H2{NiII(H2O)3}4], a Highly Symmetrical ε-Keggin Unit Capped with Four NiII Centers:  Synthesis and Magnetism

Abstract: The novel title compound {NiII 4MoV 12} demonstrates the concept of generating targeted spin topologies using reduced polyoxometalates:  The four electrophilic nickel centersforming a tetrahedronare fixed by a nucleophilic highly reduced diamagnetic ε-Keggin cluster of T d symmetry generated in solution. This cluster not only has a structural role but actually participates in the transmission of the exchange interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 14 publications
2
87
2
Order By: Relevance
“…18 Because the structure of {Ni 4 Mo 12 } is almost perfectly tetrahedral one might anticipate that the magnetic energy levels are reasonably well described by an isotropic Heisenberg model with a single antiferromagnetic exchange parameter. 19 Such a Hamiltonian can be expressed in terms of the total spin: II ion in an octahedral ligand field is s = 1. For antiferromagnetic coupling (J < 0) the resulting low-temperature magnetization curve M(B) that follows from (1) displays four steps before reaching saturation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Because the structure of {Ni 4 Mo 12 } is almost perfectly tetrahedral one might anticipate that the magnetic energy levels are reasonably well described by an isotropic Heisenberg model with a single antiferromagnetic exchange parameter. 19 Such a Hamiltonian can be expressed in terms of the total spin: II ion in an octahedral ligand field is s = 1. For antiferromagnetic coupling (J < 0) the resulting low-temperature magnetization curve M(B) that follows from (1) displays four steps before reaching saturation.…”
Section: Introductionmentioning
confidence: 99%
“…8. Our prompt-gamma neutron activation analysis showed that about 50% hydrogen was substituted by deuterium.…”
Section: Methodsmentioning
confidence: 84%
“…Distances between Ni 2+ ions within a cluster are 6.69, 6.70, 6.62, and 6.60Å, whereas the shortest distance between Ni 2+ ions that belong to different clusters is 7.15Å. Previous bulk property measurements using bulk susceptibility, high field magnetization, electron paramagnetic resonance, optical conductivity, and magneto-optical response [8][9][10] showed that the dominant interaction in the system is antiferromagnetic, which is due to the superexchange interaction through the Ni-O-Mo-ONi bonds. 9 The most interesting property of the Ni 4 nanaomagnet is an adiabatic change with non-equidistant steps observed in the magnetization measurements as a function of external magnetic field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This also explains why, compared with the α and β isomers, the γ, δ, and ε structures are relatively unstable in the condensed phase. The γ isomers of select tungstates have previously been synthesized and isolated [41][42][43][44], and a few studies have reported the synthesis and characterization of ε-Keggin isomers with encapsulated ions [45][46][47].…”
Section: Structural Isomers Of Keggin Anionsmentioning
confidence: 99%